Gen 1,1 in der Rezeption von Raschi und die Rezeption der Rezeption der Rezeption ... - Ragacs, Ursula (Protokolle zur Bibel, 2013)
The paper starts with the definition of reception as an individual process of understanding a text. Using Rashi’s commentary to Gen 1:1 as a starting point the author analyzes the texts of two medieval commentators and several modern recipients of Rashi’s text. As her conclusion of this analysis the author formulates that although the fact of reception as an individual process can be identified the motivation lying behind this process nevertheless remains invisible.